2012
DOI: 10.1002/ps.2302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quinestrol and levonorgestrel on populations of plateau pikas, Ochotona curzoniae, in the Qinghai‐Tibetan Plateau

Abstract: Single baiting of quinestrol in early breeding season reduced the reproduction and population size of pikas throughout 2007. The effect of infertility lasted into the next breeding season through a cross-year effect, which resulted in a significant reduction of population size in 2008. Quinestrol is a very promising non-lethal approach to managing pika populations; however, several factors need to be investigated further to improve the practicality of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(82 citation statements)
references
References 34 publications
5
76
0
1
Order By: Relevance
“…In addition, levonorgestrel and quinestrol have been successfully used as contraceptives for rodents such as plateau pikas (Ochotona curzioniae) and Mongolian gerbils (Meriones unguiculatus) (e.g. Liu et al 2012;Fu et al 2013).…”
Section: Hormonal Methodsmentioning
confidence: 99%
“…In addition, levonorgestrel and quinestrol have been successfully used as contraceptives for rodents such as plateau pikas (Ochotona curzioniae) and Mongolian gerbils (Meriones unguiculatus) (e.g. Liu et al 2012;Fu et al 2013).…”
Section: Hormonal Methodsmentioning
confidence: 99%
“…Results in other small mammal species are equivocal (review by Tobin and Fall). Fertility control agents could be applied on a large scale, and they have been shown to slow population growth in small mammals . Side effects associated with some methods available are prohibitive for field use, and it is difficult to achieve long‐lasting effects via oral application …”
Section: Common Volesmentioning
confidence: 99%
“…However, other species have generated different results. Our previous studies have shown that the administration of quinestrol in plateau pikas (Ochotona curzoniae) leads to male infertility for the entire breeding season (approximately 2 months), with sharp decreases in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 Male fertility recovery of estrogen treatment 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 serum testosterone level (Liu et al 2012a). In laboratory rats, administration of quinestrol had a much weaker effect, and serum testosterone did not significantly change 7 days after the estrogen treatment ended (Liu et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…The mixture (coded as EP-1) has been shown to have anti-fertility effects on several wild rodent species, such as Brandt's voles (Lasiopodomys brandti) (Zhang et al 2004;Zhao et al 2007), gray hamsters (Cricetulus migratorius) (Zhang et al 2004), midday gerbils (Meriones meridianus) (Zhang et al 2004), greater long-tailed hamsters (Tscherskia triton) (Zhang et al 2005(Zhang et al , 2006, Djungarian hamsters (Phodopus campbelli) (Wan et al 2006), Mongolian gerbils (Meriones unguiculatus) (Huo et al 2007) and field rats (Rattus nitidus) (Liu et al 2013). Under field conditions, EP-1, especially quinestrol, was found to significantly decrease the reproduction of plateau pikas (Ochotona curzoniae) (Liu et al 2012a) and Mongolian gerbils (Fu et al 2013). However, the duration of infertility in rodents after treatment with EP-1 has not been well studied.…”
Section: Introductionmentioning
confidence: 99%